HUBUNGAN PENGETAHUAN IBU HAMIL DENGAN KEJADIAN ANEMIA DI PUSKESMAS PAYUNG SEKAKI PEKANBARU - Pesa, Yadriati Maya; Anita, Wan; Yulita, Emi; Wahyuni, Romy; Masfufa, Tentya Indah; Ayumi, Nuzul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Anemia is a condition when the number of red blood cells is lower than the normal number. Every day 830 mothers worldwide (38 women in Indonesia, based on AKI 305) die from diseases related to pregnancy and childbirth. The incidence of anemia in pregnant women in Riau Province increased in 2022 (35%), 2021 (15%), 2020 (45%), 2019 (39%).The purpose of the study was to determine the relationship between the knowledge of pregnant women and the incidence of anemia at the Payung Sekaki Health Center in Pekanbaru. This study is a quantitative research with a cross sectional approach. The research was carried out at the Payung Sekaki Health Center in Pekanbaru, conducted in March-August 2024 with a sample of 68 respondents. The results showed that 5 people (7.4%) had good knowledge, 13 people (19.1%) had sufficient knowledge and 50 people (73.5%) had poor knowledge. Respondents who experienced anemia amounted to 43 people (63.2%) and did not experience anemia amounted to 25 people (36.8%). The results of the Chi-Square Test obtained P value = 0.000 < 0.05 indicating a relationship between the knowledge of pregnant women and the incidence of anemia. It is recommended that pregnant women be more active in exploring information about the incidence of anemia in pregnancy and also know how to prevent it so that pregnant women stay healthy and avoid anemia. Health workers should be more active in providing health education to the public about mothers, especially about anemia in pregnancy.Keywords: Knowledge of pregnant women, Incidence of anemia